The Impact of Accountability and Transparency on Financial Report Quality (Case Study at the Regional Office of the Ministry of Religious Affairs, Gorontalo Province) - Usman; Ayu Rakhma Wuryandini; Mutiara Istyatun Anyo (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of accountability and transparency on the quality of financial statements at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province. The background of this research is based on the importance of financial statement quality as a form of public accountability in realizing good governance. The phenomenon of significant fluctuations in balance sheet accounts, increasing operational deficit reports, and inconsistencies in financial disclosure indicate that there are still problems in the implementation of accountability and transparency principles. This study uses a quantitative approach with a survey method through distributing questionnaires to employees involved in the management and preparation of financial statements. The data were analyzed using multiple linear regression analysis techniques to determine the effect of each variable on the quality of financial statements. The results of this study are expected to provide an overview of the importance of implementing accountability and transparency in improving the quality of financial statements that are relevant, reliable, understandable, and comparable in accordance with Government Accounting Standards (SAP). In addition, this study is expected to become an evaluation material for government institutions in strengthening a transparent and accountable financial management system and increasing public trust in the management of state funds.